Impact of rising CO2 and temperature on grass phenology, physiology, and pollen release patterns in northern latitudes - Tossavainen, Tarleena; Kivimäenpää, Minna; Martikainen, Maria-Viola; Leskinen, Ari; Heinonen, Tiina; Pessi, Anna-Mari; Louna-Korteniemi, Maria; Pätsi, Sanna; Komppula, Mika; Saarto, Annika; Roponen, Marjut (Elsevier BV, 2025)
Climate change has complex effects on vegetation, including native grasses and those used as fodder plants. Like many other plant species, grasses respond to climate change by altering their phenology and physiological behavior, leading to changes e.g. in growth, reproduction and metabolic processes. Our study is the first to explore how Phleum pratense and Alopecurus pratensis respond to rising CO2 and temperatures projected for northern latitudes for two growing seasons. We investigated growth, phenology, pollen release, and physiological parameters in plants cultivated under these conditions, simulated within environmentally controlled chambers. Treatment with elevated temperature reduced the number of generative tillers and, consequently, decreased both the number of inflorescences and the season pollen integrals. Pollen release from P. pratense started up to 17 days earlier, and the daily peak concentration of released pollen was observed 1–2 h earlier in chambers with elevated temperatures when compared to the present climate conditions. Similar effects were noted in A. pratensis. Elevated CO2 (EC) increased net photosynthesis of P. pratense, but this effect was reduced under elevated temperature (ET), suggesting an antagonistic interaction. In A. pratensis, both elevated CO2 and temperature had an additive effect on increasing net photosynthesis, with the highest rate observed under the combined ETEC treatment. The elevated temperature or CO2 did not affect the plant biomass. Our findings propose that the rising temperatures in northern latitudes decrease the flowering of studied grasses and shift the seasonal and daily start of the pollen release. Changes in tiller proportions, reduced pollen integrals, and fewer inflorescences suggest that a warmer climate may negatively impact reproductive success, ecological fitness, and allergenic burden of these grasses.